Bibliometric Analysis on Decontamination of Chemical Warfare Agents in Last Thirty Years. Issue 1 (August 2021) - Huang, Xingqi; Chen, Jingfei; Zhao, Ting; Jin, Yanren; Yan, Chunxiao; Wu, Yue; Zhang, Lingxuan
Abstract: Occurrence of large-scale biochemical wars is of little possibility today, but the international chemical security situation is still not optimistic. Effective decontamination of chemical warfare agents has received close attention, becoming a global necessity. In this paper, data in the Web of Science Core Collection database were selected to systematically investigate the relevant literature about the research progress on decontamination of chemical warfare agents from 1990 to 2020. Origin Pro 2019b and CiteSpace were conducted for multi-dimensional bibliometric analysis on literature type distribution, number of annual publications, countries, institutions, journals, authors, literature co-citation and citation bursts. By August 1, 2020, there are 2, 602 papers related have been published and the number of annual publications shows a linear growth tendency. Amongst all 71 countries, United States is the country with the most publications as well as the largest centrality value. US ARMY ranks fourth in the number of publications while with the highest institution-based cooperation. "Nerve agents and blister agents", "metal-organic frameworks" and "applications of metal-organic frameworks" are prevailing in recent years, which highlights the latest development direction and research frontiers. This article promotes scientific predictions and impact assessments of decontamination of chemical warfare agents.